RANCANG BANGUN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU DI SDN LEGOK 3 MENGGUNAKAN METODE WATERFALL - Ryan Hidayat; Farizi Ilham; Muhammad Fatih Amri; Muhammad Syauqi Nadhifasla Waluyo (Journal of Research and Publication Innovation, 2026)
The process of accepting new students (PPDB) at SDN Legok 3 has traditionally been manual, using paper forms and a large book for recording. This approach often causes problems, particularly discrepancies between the data on the family cards of parents/guardians and the central data held by the Department of Population Registration and Civil Status. The accumulation of physical files also fills the administrative office and slows down the search for documents. To address these issues, this study has designed a website-based PPDB information system using PHP programming language, Laravel framework, and MySQL database. Data was collected through field observations, interviews with school staff, and literature studies. The system built has features including a school profile page, a self-registration form, a facility to upload documents (birth certificate and family card), and a panel for school operators to verify data. As an added value in its development, the PPDB system is integrated directly with the school's existing digital attendance system. Through this integration, admins can use one central dashboard to manage both student enrolment and attendance data, eliminating the need for dual systems and reducing administrative workload. Pendaftar juga dapat mengunduh bukti pendaftaran secara langsung. On the other hand, the system can automatically generate reports on enrolment data in Excel or PDF format.